A case study of public relations in Project 8 Public Library - Calizo, Lorena Vera S. (2004)
This study aims to match the user's needs to the library services in one community and come up with a public relations program appropriate to the library's capability and resources. From the community, in this particular case Project 8, the researcher tries to ascertain the users' needs and attempt a profile. The resources and operations of the Project 8 Branch library is studies.